Distribusi dan Kelimpahan Drosera serta Hubungannya dengan Mikrohabitat dan Mikroklimat di Pulau Belitung: Distribution and Abundance of Drosera in Relation to Microhabitat and Microclimate on Belitung Island - Rizal Kuwatus Salam; Nunik Sri Ariyanti; Sulistijorini; Yulian Fakhrurrozi (Departemen Biologi, Institut Pertanian Bogor, 2026)
Drosera is commonly found in nutrient-poor habitats such as heath forests on Belitung Island. This study aimed to inventory and map the distribution of Drosera species, analyse habitat floristic composition, and examine the influence of microhabitat and microclimate factors on their abundance. Field surveys were conducted using an exploratory method, and data on species abundance, vegetation composition, microhabitat, and microclimate were collected using quadrat plots at five locations. Pearson correlation analysis was used to assess relationships between Drosera abundance and environmental variables. Two species, D. burmanni and D. spatulata, were recorded in habitats with low species richness (21 species from 14 families), dominated by Leptospermum polygalifolium, Melaleuca cajuputi, and Calophyllum lanigerum. Understory vegetation included Baeckea frutescens, Rhodomyrtus tomentosa, and herbaceous species from Cyperaceae, Eriocaulaceae, and Poaceae. Drosera occurred on clay, quartz sand, and rocky substrates, with D. spatulata more common on clay and D. burmanni on quartz sand. Drosera abundance was significantly influenced by soil moisture, soil acidity, and understory density, but not by understory cover. These findings highlight the importance of microhabitat and microclimate in shaping Drosera distribution and abundance.